2022
DOI: 10.1177/23493003221082333
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents to Child Placement in Residential Care: A Systematic Review

Abstract: Individual studies suggest most children and youth in residential care centres (RCCs) have living parents, and parental death is not the primary antecedent to placement in residential care. The goal of the present review was to examine the literature to better understand the primary antecedents to placement in RCCs overall. One hundred thirty-two studies, including 60,683 children in 47 nations meet eligibility criteria for inclusion for the overarching review of antecedents of placement. Primary information s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Care leavers are widely recognized as a vulnerable population (Berens & Nelson, 2015 ; Bondi et al, 2020 ; van Breda et al, 2020 ; Wilke et al, 2022 ). Research has consistently found that care leavers are more likely to have experienced high levels of adverse childhood experience (ACEs) and are at significantly greater risk for negative outcomes (Felitti et al, 1998 ; Simkiss, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Care leavers are widely recognized as a vulnerable population (Berens & Nelson, 2015 ; Bondi et al, 2020 ; van Breda et al, 2020 ; Wilke et al, 2022 ). Research has consistently found that care leavers are more likely to have experienced high levels of adverse childhood experience (ACEs) and are at significantly greater risk for negative outcomes (Felitti et al, 1998 ; Simkiss, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research suggests reintegrations should be supported by thorough family assessment, child and family preparation, and a graduated approach to contact. Service providers should work with families to resolve concerns that preceded child placement in residential care prior to reintegration (Schrader-McMillan & Herrera, 2016; Wilke, et al, 2022). Further, all children and families experiencing reintegration should receive support and monitoring (Corcoran & Wakia, 2016).…”
Section: Risks Of Rapid Unprepared Returnmentioning
confidence: 99%
“…However, the measures taken to prevent the spread of the virus, such as mandated social isolation, resulted in other consequences. As is often the case with systemic issues, those who were already vulnerable have been disproportionately affected (Hillis et al, 2021; Wilke et al, 2020b)…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that reintegration should be supported by thorough family assessments, preparations for both the child and family, and a gradual approach to contact and supervision (Delap & Wedge, 2016). Service providers should collaborate with families to address concerns that led to the child’s placement in residential care before reintegration (Jedwab et al, 2018; Schrader-McMillan & Herrera, 2016; Wilke et al, 2022b). Additionally, all children and families undergoing reintegration should receive support and monitoring (Corcoran & Wakia, 2016).…”
Section: Introductionmentioning
confidence: 99%